2021
DOI: 10.1108/sbm-04-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting the formation of esports gameplay intention: interaction effects of genre and gender

Abstract: PurposeWhile each genre and gender has been revealed as significant moderators for esports gameplay intention, exploring the interaction effects between genre and gender could broaden our understanding of the drivers’ relative effects on esports gameplay intention. Thus, the purpose of this study is to examine the interaction effects of gender and genre in the relationship between esports gameplay intention and its drivers (i.e. hedonic motivation, habit, price value, effort expectancy, social influence and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Building on this ESC model , Jang et al (2020b) showed mediation effects of eSports live streaming between recreational gameplay and eSports events broadcast consumption. In another follow-up study, Jang et al (2021) showed an interaction effect of game genre and gender as moderators of the relationships between gameplay intention and its determinants.…”
Section: Research On Esports Consumptionmentioning
confidence: 92%
“…Building on this ESC model , Jang et al (2020b) showed mediation effects of eSports live streaming between recreational gameplay and eSports events broadcast consumption. In another follow-up study, Jang et al (2021) showed an interaction effect of game genre and gender as moderators of the relationships between gameplay intention and its determinants.…”
Section: Research On Esports Consumptionmentioning
confidence: 92%
“…Thus: (Wang, 2014), and team member selection (Lou et al, 2020). Jang et al (2021) found that female gamers exhibit more resilience and less risk-taking behaviour compared to male gamers when engaging with new games. Males are less motivated to participate in gamified self-efficacy and workplace health programs (Lier and Breuer, 2020;Polo-Peña et al, 2021), but they are more willing to engage with new technologies (Alshurideh et al, 2021;Gumz and Fettermann, 2021).…”
Section: Ejmbementioning
confidence: 99%
“…They found the model generally operated across the three exclusive genre category groups. Another study (Jang et al, 2021c) used a two-way MANOVA (Multivariate Analysis of Variance) to determine the impact of the six groups based on the interaction of gender (i.e. male and female) and the three genres' categories (i.e.…”
Section: Five Clusters: Definitions By Playtime and Genresmentioning
confidence: 99%